The penny mansions - Mayfield, Steven (Regal House Publishing, 2023)
"With the Spanish flu pandemic on the rise, a former gold rush town-- once the largest city in the Pacific Northwest-- is threatened with extinction via eminent domain should their population fall below 125 citizens. To save their homes, former madam Maude Dollarhyde, her mixed-race grand-daughter, Bountiful, and their fellow council members agree to sell four abandoned mansions for a penny apiece if the buyers will stay in town long enough to be counted in the 1920 census. Soon, an eclectic cast of newcomers arrives, including a New York actor and his questionably-familial family; a lawyer with an agoraphobic wife, mute son, and austere nanny; six excommunicated Mormons; and the great-nephew of the town' s hated former boss. As real estate developer and politician Gerald Dredd plots to foil the council' s plan, the new families move in and knock over the first domino in a row that includes three romances, twelve sticks of dynamite, an unintentionally hilarious community theater production, an investigation by a Chicago insurance detective, and last of all, murder!"--Amazon.